Levels of eotaxin-3 as a noninvasive biomarker for monitoring the treatment EoE in school age children with food allergy - Stencel-Gabriel, Krystyna; Kula-Gradzik, Joanna; Parszewski, Łukasz; Majda, Anna (Journal of Education, Health and Sport, 2017)
Introduction Study in which we found a significant and specific alteration of eotaxins-3 in active EoE childrens with food allergy. Aim The aim of the study was to identity eotaxin-3 that correlated with activity of EoE as measurmed by esophageal eosinophilia and response to treatment by using elimination diet in children group with food allergy in the course of EoE. Material and methods Five childrens ranging in age from 12 to 18 years with EoE and food allergy was studied for up to 12 weeks of used eliminate food to which the children are sensitized. Biomarker (eotaxin-3 / CCL26) in serum were analyzed as to their use as a noninvasive biomarker for the diagnosis and assessment of EoE disease status. Results Eotaxin-3 levels correlated significantly with all investigated clinical parameters: blood eosinophils levels ( r=0,80,p<0,01), eosinophils in thissue biopsy ( r=0,66, p<0,01) and IgE levels (r=0,34,p<0,05) from EoE patients. Conclusions Eotaxin-3 might constitute a pathogenic player in tissue eosinophilia and subsequent esophagus damage, and a biomarker for disease activity and interesting therapeutic target in EoE.